Exploring Environmental Issues in Children's Literature: An Ecocritical study of Zhang Wei's Works - Yang, Yi (Archīum Ateneo, 2024)
Zhang Wei is one of the most influential authors in contemporary Chinese literature. His earlier works were written for adults, but he has recently contributed to children’s literature as well. While each of his children’s books has its own original storylines, they share a strong interest in environmental issues and contain some obvious themes of ecological consciousness. Peninsular Ha Li Ha Qi, which was influenced by Henry David Thoreau’s Walden, is a kind of pastoral literature. Looking for the Fish King, on the other hand, deals with “toxic discourse,” informing children about the life-destroying evils of modern industrial technology. Last but not least, The Youth and the Sea demonstrates the author’s solutions to the ecological crisis by highlighting children’s wisdom, non-human-centered environmental ethics, and the ecocentric mode. This type of ecological children’s literature constitutes a unique category within contemporary Chinese literature. It both widens the ambit of children’s literature and builds a bridge between such literature and ecological criticism. Further, it can also be considered important material while examining the author’s ecological consciousness. Hence, this paper takes ecocriticism as its main methodology, discusses three distinct themes of Zhang’s ecological children’s literature—namely, pastoralism, toxic discourse, and ecocentrism based on animism—and analyzes how they make a literary contribution to current ecological discourses by means of presenting different ways of dealing with environmental issues.